Lives on hold: A qualitative synthesis exploring the experience of chronic low-back pain - Bunzli, Samantha; Watkins, R.; Smith, Anne; Schϋtze, R.; O'Sullivan, Peter (Lippincott Williams and Wilkins, 2013)
Objectives: Chronic nonspecific low-back pain (CLBP) is a prevalent, costly condition that is remarkably resistant to intervention. Substantial evidence suggests that a mismatch exists between the biomedical beliefs held by clinicians and patients and the bio psychosocial nature of CLBP experience. The aim of this metasynthesis of qualitative studies was to provide clinicians with a richer understanding of their patients’ CLBP experience to highlight the importance of moving away from biomedical paradigms in the clinical management of CLBP.Methods: Qualitative studies exploring the CLBP experience from the perspective of the individual were included. Twenty-five articles representing 18 studies involving 713 participants were subjected to the 3-stage analytic process of extraction/coding, grouping, and abstraction.Results: Three main themes emerged: the social construction of CLBP; the psychosocial impact of the nature of CLBP; and coping with CLBP.Discussion: The authors conceptualize the experience of CLBP as biographical suspension in which 3 aspects of suspension are described: suspended “wellness,” suspended “self,” and suspended “future”. The implications of improved clinician understanding of the CLBP experience and directions for future research are discussed.